Textile design department: open masking technique - Naser, Faradiba Liana; Rosman, Rahman; Norazalee, Muhammad Ashsyahmy; Che Mansor, Mohamad Syahril Ikhwan; Rosli, Muhamad Afiq Afnan (College of Creative Arts, 2023)
This workshop was conducted by Mr. Rahman Rosman, and three from textile department students. The open masking technique are commonly used in textile printing and in various industrial applications to create a repeated pattern or design on fabric. In textile printing, open masking technique also known as “eco-printing” or “botanical printing”. It involves placing natural materials such as leaves, flowers, and bark onto fabric and then using the open masking technique with a silk screen frame to print directly onto the fabric. This technique can produce a wide range of effects depending on the type of natural materials used and the way they are arranged on the fabric. It is often used to create one-of-a-kind textiles and clothing items that have a natural and rustic feel. Through these hands-on workshops, it provides numerous benefits for the students.